1990
DOI: 10.1152/ajpregu.1990.258.2.r388
|View full text |Cite
|
Sign up to set email alerts
|

Renin secretion by fetal lamb kidneys in vitro

Abstract: We studied the content and secretion of renin by renal cortical slices obtained from ovine fetuses at 0.62-0.77 gestation (n = 5 immature) and at 0.84-1.00 gestation (n = 5 mature). Renin content of fresh slices and renin secretion after the incubation of slices in Robinson's medium with or without isoproterenol or dibutyryl (DB) adenosine 3',5'-cyclic monophosphate (cAMP) (10(-4)-10(-8) M) were measured. Renin content of immature fetal kidneys (ng.ml homogenate-1.h-1.mg-1) and basal renin secretion rate [ng (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…It is of interest that denervation in late gestation resulted in low basal levels of plasma renin and decreased sensitivity to isoproterenol despite normal renal renin concentration. This mimics the pattern of renin secretion seen in early gestation fetuses (24) and may represent withdrawal of some sort of "priming" effect of the renal nerves to sensitize cells destined to secrete renin in late gestation. Exactly how this priming effect would occur is unknown, but Slotkin et al (29) have suggested that early pioneer synapses provide a trophic signal that enables cells to increase their sensitivity to stimulation during the perinatal transition period (30).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…It is of interest that denervation in late gestation resulted in low basal levels of plasma renin and decreased sensitivity to isoproterenol despite normal renal renin concentration. This mimics the pattern of renin secretion seen in early gestation fetuses (24) and may represent withdrawal of some sort of "priming" effect of the renal nerves to sensitize cells destined to secrete renin in late gestation. Exactly how this priming effect would occur is unknown, but Slotkin et al (29) have suggested that early pioneer synapses provide a trophic signal that enables cells to increase their sensitivity to stimulation during the perinatal transition period (30).…”
Section: Discussionmentioning
confidence: 62%
“…Plasma active renin and prorenin concentrations (ARC and PRC, respectively) were determined by a modification of previously described methods (24). Plasma ARC was measured as a function of the amount of ANG I generated in the presence of excess angiotensinogen (nephrectomized sheep plasma).…”
Section: Measurement Of Active Renin and Proreninmentioning
confidence: 99%
“…bpm, Beats/min. upregulation of the RAS in the perinatal period may be related to the increase in COX-2 expression observed at this time (32,43).…”
Section: Discussionmentioning
confidence: 93%
“…Animal studies have found immunoreactive COX-2 to appear first in midgestation (15,41). Furthermore, gestational agedependent responses in renin secretion have been observed in the presence of stimuli such as hemorrhage, hypoxia, furosemide infusion, hypotension, and isoproterenol infusion (9,30,(32)(33)(34)(35). However, chronic stimulation of the RAS can induce renin secretion in immature animals to a pattern resembling that of more mature fetuses (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation